Effects of Fluorescein Staining on Laser In Vivo Confocal Microscopy Images of the Cornea - Christine W. Sindt; D. Brice Critser; Trudy K. Grout; Jami R. Kern (Journal of Ophthalmology)
This study was designed to identify whether topical fluorescein, a common ophthalmic tool, affects laser in vivo confocal microscopy of the cornea, a tool with growing applications. Twenty-five eye care specialists were asked to identify presence or absence of fluorescein in 99 confocal micrographs of healthy corneas. Responses were statistically similar to guessing for the epithelium (48% ± 14% of respondents correct per image) and the subbasal nerve plexus (49% ± 11% correct), but results were less clear for the stroma. Dendritic immune cells were quantified in bilateral images from subjects who had been unilaterally stained with fluorescein. Density of dendritic immune cells was statistically similar between the unstained and contralateral stained eyes of 24 contact lens wearers (P=.72) and of 10 nonwearers (P=.53). Overall, the results indicated that fluorescein staining did not interfere with laser confocal microscopy of corneal epithelium, subbasal nerves, or dendritic immune cells.